Perhitungan Respons Elektromagnetik Lapisan Tipis Heterogen Menggunakan Metoda Persamaan Integral - Hendra Grandis; Nanang T. Puspito (Jurnal Matematika & Sains, 1998)
The computation of electromagnetic response of a 3-D model which represents subsurface electric conductivity distribution is done by resolving the Maxwells equations using the integral equation method. In order to simplify the problem, it is assumed that the 3-D inhomogeneity is confined in a thin layer embedded in a horizontally stratified (1-D) medium. The algorithm is applied to compute the response of two simple models containing either resistive and conductive inhomogeneity. The apparent resistivity, phase and magnetic transfer function give general features of the models.